Selections from the prison notebooks of Antonio Gramsci - Hoare, Quintin; Nowell Smith, Geoffrey (London: Lawrence and Wishart, 1971)
"edited and translated by Quintin Hoare and Geoffrey Nowell Smith Bibliotheek François Vercammen"